First-principles calculation of twin boundary energy and strength/embrittlement in hexagonal close-packed titanium. (January 2022) - Hui, Jun; Zhang, Xiaoyong; Liu, Tao; Liu, Wenguan; Wang, Biao
Graphical abstract: Highlights: Perfect prediction of the strengthening and embrittling of twins. Explains the relationship between Voronoi volume and segregation energy. The atomic radius is closely related to the twin formation energy. Abstract: We performed first-principles calculations to determine the effects of 14 metallic solutes on twin boundary (TB) energy and strength/embrittlement in Ti alloys, with Ti {1 0  1 ¯  2} and {1 0  1 ¯  1} TBs as models. Twin formation energies were calculated to identify the effects of solutes on TB stability. Segregation energy and the associated segregation concentration and solubility energy were examined to identify the existence states of the solutes. The influences of solutes on TB strength were identified through strengthening/embrittling energy and its mechanical and chemical contributions. Tensile tests were performed using the "uniaxial-strain loading" and the "uniaxial-stress loading" methods to determine maximum TB strength.